Photocrosslinkable gelatin hydrogel for epidermal tissue engineering - Zhao, Xin; Lang, Qi; Yildirimer, Lara; Lin, Zhi Yuan; Cui, Wenguo; Annabi, Nasim; Ng, Kee Woei; Dokmeci, Mehmet R.; Ghaemmaghami, Amir M.; Khademhosseini, Ali (Wiley, 2016)
Natural hydrogels are promising scaffolds to engineer epidermis. Currently, natural hydrogels used to support epidermal regeneration are mainly collagen- or gelatin-based, which mimic the natural dermal extracellular matrix but often suffer from insufficient and uncontrollable mechanical and degradation properties. In this study, a photocrosslinkable gelatin (i.e., gelatin methacrylamide (GelMA)) with tunable mechanical, degradation, and biological properties is used to engineer the epidermis for skin tissue engineering applications. The results reveal that the mechanical and degradation properties of the developed hydrogels can be readily modified by varying the hydrogel concentration, with elastic and compressive moduli tuned from a few kPa to a few hundred kPa, and the degradation times varied from a few days to several months. Additionally, hydrogels of all concentrations displayed excellent cell viability (>90%) with increasing cell adhesion and proliferation corresponding to increases in hydrogel concentrations. Furthermore, the hydrogels are found to support keratinocyte growth, differentiation, and stratification into a reconstructed multilayered epidermis with adequate barrier functions. The robust and tunable properties of GelMA hydrogels suggest that the keratinocyte laden hydrogels can be used as epidermal substitutes, wound dressings, or substrates to construct various in vitro skin models.